Hubungan Persepsi Terhadap Organisasi dan Motif Sosial dengan Minat Berorganisasi - Purwanto, Aldi; Hidayati, Ira; Qohar, Abdul; Tajuddin, Nilawati (Universitas Islam Negeri Raden Intan Lampung, 2022)
IInterest in organization is the existence of interest from students to participate in and choose to be active in an organization that makes a person have a tendency to pay attention to the activities of the organization he chooses based on encouragement from within. Perceptions of the organization and social motives are factors that influence the occurrence of organizational interest. This study aims to determine the relationship between perceptions of organization and social motives with organizational interest in the ushuluddin faculty and religious studies. Researchers used quantitative research methods with precision sampling techniques and the samples in this study were 70 students who joined the Study Program Student Association (HMPS). Data collection techniques in this study used a psychological scale including a scale of organizational interest, perception of the organization and social motives. The scale of organizational interest is 21 items (α = 0.905), the perception of the organization is 21 items (α = 0.880), and the social motive is 19 items (α = 0.866). The analysis technique used is a multiple regression analysis technique assisted by the SPSS 21.0 for windows program. The analyzed data shows the results: The results showed that the value of Rx1.2.3-y = 0.542, the value of F = 13.951 on the significance of p = 0.000 and stated (p < 0.01). The results obtained that the perception of the organization and social motives provide an effective contribution of 29.4% to the dependent variable and 70.6% generated by other variables outside the study. Based on the calculation results obtained the value of rx1-y = 0.459 and p = 0.000 (p <0.05). The results obtained indicate that there is a relationship between perceptions of the organization and interest in the organization. The results obtained stated that the perception variable towards the organization received an effective contribution of 16.7% to the interest in organization. Based on the calculation results obtained the value of rx2-y = 0.418 and p = 0.000 (p <0.05). The results obtained indicate that there is a relationship between social motives and organizational interest. The results obtained stated that the social motive variable received an effective contribution of 12.7% to organizational interest. Keywords: Interest in Organization, Perception of Organization, and social motives